Quantifying avian avoidance of offshore wind turbines: Current evidence and key knowledge gaps. (September 2018) - Cook, Aonghais S.C.P.; Humphreys, Elizabeth M.; Bennet, Finlay; Masden, Elizabeth A.; Burton, Niall H.K.
Abstract: The risk of collision between birds and turbines is seen as one of the key issues in the planning process for offshore wind farms. In some cases, predictions of collision risk have led to projects either being withdrawn from the planning process, or refused planning consent. Despite this, the evidence base on which collision risk is assessed is extremely limited and assessments rely on models which can be highly sensitive to assumptions, notably about bird collision avoidance behaviour. We present a synthesis of the current state of knowledge about collision risk and avoidance behaviour in seabirds. Evidence suggests species-specific responses to turbines and that in order to avoid collision, most birds adjust their flight paths at some distance from the turbines, rather than making last-second adjustments. We highlight the key gaps in knowledge and make recommendations for future data collection. Highlights: Seabird collisions with turbines are seen as a key concern for the offshore wind industry. Understanding the extent to which seabirds avoid turbines is a key part of the impact assessment process. We synthesise the knowledge of seabird interactions with offshore wind turbines. We highlight that most avoidance behaviour is likely to take place away from the turbines. We identify the key remaining gaps in knowledge and discuss the most appropriate approaches to fill these gaps.